Automatic Near‐Real‐Time Detection of CMEs in Mauna Loa K‐Cor Coronagraph Images. Issue 10 (11th October 2017) - Thompson, W. T.; St. Cyr, O. C.; Burkepile, J. T.; Posner, A.
Abstract: A simple algorithm has been developed to detect the onset of coronal mass ejections (CMEs), together with speed estimates, in near‐real time using linearly polarized white‐light solar coronal images from the Mauna Loa Solar Observatory K‐Cor telescope. Ground observations in the low corona can warn of CMEs well before they appear in space coronagraphs. The algorithm used is a variation on the Solar Eruptive Event Detection System developed at George Mason University. It was tested against K‐Cor data taken between 29 April 2014 and 20 February 2017, on days identified as containing CMEs. This resulted in testing of 139 days' worth of data containing 171 CMEs. The detection rate varied from close to 80% when solar activity was high down to as low as 20–30% when activity was low. The difference in effectiveness with solar cycle is attributed to the relative prevalence of strong CMEs between active and quiet periods. There were also 12 false detections, leading to an average false detection rate of 8.6%. The K‐Cor data were also compared with major solar energetic particle (SEP) storms during this time period. There were three SEP events detected either at Earth or at one of the two STEREO spacecraft when K‐Cor was observing during the relevant time period. The algorithm successfully generated alerts for two of these events, with lead times of 1–3 h before the SEP onset at 1 AU. The third event was not detected by the automatic algorithm because of the unusually broad width in position angle. Key Points: Coronal mass ejections are detected in near‐real‐time Coronal mass ejection detections are used to warn of possible solar energetic particle events Coronal mass ejections are detected automatically using ground observatory data